West African Crystalline Maculopathy in Sickle Cell Retinopathy - Jennifer S. Kung; Theodore Leng (Case Reports in Ophthalmological Medicine)
Purpose. To describe the first reported case of West African crystalline maculopathy (WACM) from a member of the Benin tribe and explore the association with sickle cell retinopathy. Methods. Full ophthalmic examination and high-resolution ocular coherence tomographic imaging. Patients. 61-year-old patient from an academic retina practice. Results. The patient demonstrated bilateral yellow-green birefringent crystals localized to the inner retina on optical coherence tomography, as well as sickle cell-related neovascularization in the right eye. She reported no consumption of kola nuts. Conclusions. Associated retinal vascular disease may be important in the pathogenesis of crystalline maculopathy.